2021
DOI: 10.15678/eber.2021.090410
|View full text |Cite
|
Sign up to set email alerts
|

Economic determinants of total factor productivity growth: The Bayesian modelling averaging approach

Abstract: The objective of this article is to use the most recent national-level data (reflecting heterogeneity) to explore determinants of total factor productivity (TFP) growth. Research Design & Methods:The article examines the performance of a number of potential TFP growth determinants, relying on the Bayesian modelling analysis (BMA) methodology, which allows for isolating key regressors and assessing their actual contribution in relation to the phenomenon under study. As a scientific methodology, BMA is deeply ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Scientific research conducted in the twenty-first century has shown the possibility of applying production functions in the economic analysis of the activities of enterprises and entrepreneurs that operate in the agricultural sector. Production functions are economic and mathematical models of production processes and quantitatively express a stable natural relationship between factors describing capital and labor costs (Sobieraj and Metelski, 2021) and an indicator characterizing the volume of agricultural production (Parlńska and Dareev, 2011;Ahmetov et al, 2019;Petrick and Kloss, 2018). Most scientific publications considered data for a number of years (the so-called time series).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientific research conducted in the twenty-first century has shown the possibility of applying production functions in the economic analysis of the activities of enterprises and entrepreneurs that operate in the agricultural sector. Production functions are economic and mathematical models of production processes and quantitatively express a stable natural relationship between factors describing capital and labor costs (Sobieraj and Metelski, 2021) and an indicator characterizing the volume of agricultural production (Parlńska and Dareev, 2011;Ahmetov et al, 2019;Petrick and Kloss, 2018). Most scientific publications considered data for a number of years (the so-called time series).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theoretical underpinnings of this investigation lie in the vast landscape of business cycle models and empirical considerations that contribute to our understanding of economic synchrony. Keynesian models [8,9], rooted in demand-side dynamics, neoclassical models emphasizing supply-side changes [8,10], and the Real Business Cycle (RBC) model [11], highlighting the impact of technological change on productivity [12], offer distinct perspectives [8, 10,12,13]. Structural vector autoregressions (SVARs) unravel the intricate dynamics between construction and business cycles [14], while dynamic stochastic general equilibrium (DSGE) models provide a robust framework for modeling the stickiness of wages and prices affecting the construction sector [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the digital economy, T. Zhao [10] demonstrates that enhancing entrepreneurial activity has positive impact on the high-quality development of urban economy. The digital economy also has the functional characteristics of spatial effect, regional link-age, and productivity improvement [11][12][13]. J.…”
Section: Introductionmentioning
confidence: 99%